Niche heritage tourism in stingray island: The case of Japanese defense heritage in Indonesia - Chairy; Prayoga, Tasya Zahwa; Rahmiati, Filda; Goenadhi, Felix; Bakri, Mohammed Hariri (ANPAD - Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao, 2024)
Objective: The purpose of this study is to analyze the competitiveness of Morotai Island, located in North Maluku, in terms of tourism development potential. Theoretical Framework: Tourism, defined as the movement of people to increase employment opportunities, local community economies, international trade, export revenue, foreign exchange earnings and investment, is influenced by a variety of social, cultural, and economic variables. Therefore, heritage sites and historic monuments are critical to urban development because they promote a sense of community among citizens while also emphasizing local identity and location. Method: Empirical research was carried out utilizing an inductive methodology using a variety of primary and secondary data sources. Results and Discussion: Results indicate that to further strengthen the community and further its tourism and regeneration aims, it could be beneficial for the autonomous organization organizing and overseeing social and cultural events and activities. Furthemore, to develop a range of tourism supporting services, the inventiveness of the region’s tourism entrepreneurs also require training in the early stages of region’s development. Research Implications: The study implicates an overall belief that improving Morotai's urban and economic landscape through tourism will either keep locals in the area or discourage them from leaving in pursuit of better opportunities and a higher standard of living. Originality/Value: This study contributes to the community heritage-based tourism as a tool of diversifying its local economic structure. This research precisely to recognize historic-heritage area in as a strategic instrument to develop rural areas.